Personal inquiry: orchestrating science investigations within and beyond the classroom - Sharples, Mike; Scanlon, Eileen; Ainsworth, Shaaron; Anastopoulou, Stamatina; Collins, Trevor; Crook, Charles; Jones, Ann; Kerawalla, Lucinda; Littleton, Karen; Mulholland, Paul; O’Malley, Claire (Taylor & Francis, 2015)
A central challenge for science educators is to enable young people to act as scientists by gathering and assessing evidence, conducting experiments, and engaging in informed debate. We report the design of the nQuire toolkit, a system to support scripted personal inquiry learning, and a study of its use with school students ages 11–14. This differs from previous work on inquiry learning by its emphasis on learners investigating topics of personal significance supported by a computer-based toolkit to guide school pupils through an entire inquiry process that connects structured learning in the classroom with discovery and data collection at home or outdoors. Findings from the studies indicate that the toolkit was successfully adopted by teachers and pupils in contexts that included teacher-directed lessons, an after-school club, field trips, and learner-managed homework. It effectively supported the transition between individual, group, and whole-class activities and supported learning across formal and informal settings. We discuss issues raised by the intervention studies, including how the combination of technology and pedagogy provided support for the teacher despite difficulties in managing the technology and integrating field data into a classroom lesson. We also discuss the difficulty of altering young people’s attitudes to science.